COMMUNITY RELATION PERKEBUNAN KELAPA SAWIT TANAH RAWA DI KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Saladin Ghalib; Irwansyah Irwansyah; Yuanita Setyastuti; Sri Astuty (Metacommunication, 2018)
AbstractThe research objective is to identify and analyze on community relations of palm plantation companies marshland in fostering good relations and handling problems with masyarakatsekitar where previously more rampant land clearing switching function for large-scale oil palm plantations. This raises the pros and cons in the community, especially around oil palm estates. The method used in this research is descriptive method Qualitative and exploratory research.Data collection through depth interviews with semi-structured interviews with key informants and informant support. Mechanical Analysis of data using analysis phases of Miles and Huberman namely data reduction, data presentation, Draw Conclusions and Verifikasi.Validation data using triangulation and triangulation methods. The results of this study indicate that companies of oil palm plantations in the area Barito Kuala particularly in Sub Rantau Badauh and the District Cerbon not implement community relations to the maximum, where the activities of community relations is limited only to charity, CSR partnership programs plasma and plasma-core, as well as sponsorship, while for the new community development include the provision of postal services where health is not enabled, so the action and communication in fostering and addressing the problems with the local community still require a further commitment from the company.Keywords : Community Relation, Community Development, Corporate Social Responsibility, Palm Oil Abstrak Tujuan penelitian adalah untuk mengetahui dan menganalisa mengenai community relation Perusahaan Perkebunan KelapaSawit tanah rawa dalam membina hubungan baik dan menangani permasalahan dengan masyarakatsekitar dimana  sebelumnya semakin marak pembukaan lahan yang beralih fungsi untuk perkebunan kelapa sawit berskala besar. Hal tersebut menimbulkan pro kontra dalam masyarakat, khususnya masyarakat sekitar perkebunan kelapa sawit. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan  tipe  penelitian eksploratif. Teknik pengumpulan data melalui depth interview melalui wawancara semi terstruktur dengan informan kunci dan informan pendukung.Teknik Analisa data menggunakan tahapan analisa dari Miles dan Huberman yaitu Reduksi data, penyajian data, Menarik Kesimpulan danVerifikasi .Validasi data menggunakan triangulasi sumber dan triangulasi metode. Hasil Penelitian ini menunjukkan bahwa perusahaan-perusahaan perkebunan kelapa sawit di area Kabupaten Barito Kuala khususnya di Kecamatan Rantau Badauh dan Kecamatan Cerbon belum melaksanakan community relations secara maksimal, dimana kegiatan community relations masih terbatas hanya untuk kegiatan amal, CSR program kemitraan plasma dan inti plasma, serta sponsorship, sementara untuk community development baru berupa penyediaan tempat layanan pos kesehatan yang juga tidak difungsikan, sehingga sisi aksi dan komunikasi dalam membina dan menangani permasalahan dengan masyarakat sekitar masih memerlukan komitmen lebih lanjut dari pihak perusahaan.Kata kunci : Community Relation, Community Development, Corporate Social Responsibility, Palm Oil